Section Commentary. Cultural, Social, and Linguistic Aspects of School Consultation - Shriberg, David; Little, Tiondra J.; McPherson, Casey (Handbook of Research in School Consultation: Empirical Foundations for Educational and Human Sciences: Third Edition, 2026)
This chapter provides commentary on the four chapters in the section on the cultural, social, and linguistic aspects of school consultation. In each case, the authors pose penetrating insights and highlight a need for more extensive literature utilizing the full spectrum of research methodologies. In this spirit, this chapter suggests that strong consultation in these topical domains might be guided by the questions: (a) What is our mindset as researchers?, (b) Is the researcher culturally humble?, and (c) What might be most helpful? Building off the “what might be helpful” question, the commentary closes by framing two relevant areas where consultation research is lacking-consultation research in support of multiracial students and consultation research to address antisemitism and support Jewish students-as ways to expand the cultural, social, and linguistic aspects of school consultation literature. © 2026 selection and editorial matter, S. Andrew Garbacz, Daniel S. Newman, William P. Erchul, and Susan M. Sheridan; individual chapters, the contributors.
Keywords: dept.csp

The Neurospicy Queer Experience: Insights Into the Lived Experiences & Counseling Needs of Transgender and Gender Expansive Adults with ADHD - Gorski, J.; Bonjo, L.; Sassu, Kari; Councilor, KC (Journal of LGBTQ Issues in Counseling, 2026)
Keywords: ADHD; Expansive; Human sexuality; Lived experience; Qualitative research; Queer; Transgender; dept.com; dept.csp; gender affirming care; gender expansive; neurodivergence; neuroqueer; neurospicy

Professional involvement - Foss-Kelly, Louisa L.; Moorhead, Holly Hartwig (A Guide to Graduate Programs in Counseling: Second Edition, 2025)
Entering a counselor education program is just the first step in becoming a Professional Counselor, which includes developing a solid Professional Counselor identity and a plan for a fulfilling career. In this chapter, the authors provide a step-by-step plan for understanding key elements of becoming a Professional Counselor, beginning to work as a Professional Counselor, and contributing to the counseling profession. These activities include professional involvement, service, and scholarship as well as other meaningful pursuits for building one's successful career. The authors present a professional involvement pyramid to illustrate how Counselors can engage in professional identity development from graduate school throughout their careers. © Oxford University Press 2025. All rights reserved.
Keywords: Counseling; Counselor education; Professional Counselor; Professional Counselor identity; Professional development; Professional service; dept.csp

Machine learning predictive models to guide prevention and intervention allocation for anxiety and depressive disorders among college students - Zhai, Yusen; Zhang, Yixin; Chu, Zhicong; Geng, Baocheng; Almaawali, Mahmood; Fulmer, Russell; Lin, Yung-Wei Dennis; Xu, Zhaopu; Daniels, Aubrey D.; Liu, Yanhong; Chen, Qu; Du, Xue (Journal of Counseling & Development, 2024)
College student mental health has been a critical concern for professional counselors. Anxiety and depressive disorders have become increasingly prevalent over the past decade. Utilizing machine learning, a subset of artificial intelligence (AI), we developed predictive models (i.e., eXtreme Gradient Boosting [XGBoost], Random Forest, Decision Tree, and Logistic Regression) to identify US college students at heightened risk of diagnosable anxiety and depressive disorders. The dataset included 61,619 students from 133 US higher education institutions and was partitioned into a 90:10 ratio for training and testing the models. We employed hyperparameter tuning and cross-validation to optimize model performance and examined multiple measures of predictive performance (e.g., area under the receiver operating characteristic curve [AUC], accuracy, sensitivity). Results revealed strong discriminative power in our machine learning predictive models with AUC of 0.74 and 0.77, indicating current financial situation, sense of belonging on campus, disability status, and age as the top predictors of anxiety and depressive disorders. This study provides a practical tool for professional counselors to proactively identify students for anxiety and depressive disorders before these conditions escalate. Application of machine learning in counseling research provides data-driven insights that help enhance the understanding of mental health determinants, guide prevention and intervention strategies, and promote the well-being of diverse student populations through counseling.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/jcad.12543
Keywords: anxiety; depression; dept.csp; machine learning; peer-reviewed; predictive model; prevention and early intervention

Special considerations for working with parents and caregivers - Sassu, K.A. (Introducing Autism: Theory and Evidence-Based Practices for Teaching Individuals with ASD, 2024)
Parents and caregivers of individuals with autism spectrum disorder (ASD) are faced with unique challenges and stressors from the early stages of their children’s development, through subsequent diagnosis, navigating the educational and therapeutic landscapes, and into adulthood. Whether their child requires Level 1, 2, or 3 supports according to their Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition diagnosis, parents will be faced with many different types of stressors. Given their experiences and knowledge of their children, they can offer valuable insights to educators and service providers that inform interventions and lead to optimal outcomes for individuals with ASD. This chapter explores the common challenges encountered by parents and caregivers and offers suggestions for ways that professional educators can best engage with them so as to establish optimal supports for individuals with autism. © 2024 Taylor & Francis Group. All rights reserved.
Keywords: dept.csp

Transdisciplinary teaming - Eren, R.B.; Sassu, K.A. (Introducing Autism: Theory and Evidence-Based Practices for Teaching Individuals with ASD, 2024)
This chapter briefly explores the history and development of teaming in education. The three most common models of educational teaming are defined and discussed in detail. The primary focus of the chapter is on the Individuals with Disabilities Education Act-mandated multidisciplinary team and how it can be transformed into a transdisciplinary teaming model in a school setting that serves individuals with autism spectrum disorder (ASD). This transdisciplinary teaming model is student centric and stresses the importance of considering the whole child, specifically as it relates to the team’s systematic communication, goal sharing, knowledge of objectives and agenda items, and the need for ongoing clarification of knowledge among the team. The emphasis is on shared knowledge that leads to greater success of the team in meeting the needs of the student under discussion. This transdisciplinary teaming model also serves as a means to troubleshoot student challenges through a group problem-solving process. The six elements in the development of a transdisciplinary teaming model are discussed in detail. © 2024 Taylor & Francis Group. All rights reserved.
Keywords: dept.csp

Growing grassroots: counseling student experiences in legislative professional advocacy - Foss-Kelly, L.L.; Parzych, J.; Feshler, M.; Yale, J.; Chen, Q. (Journal of Counselor Leadership and Advocacy, 2024)
Counselor educators and supervisors have a vital role in promoting legislative professional advocacy (LPA). An interpretative qualitative analysis study of counseling graduate students involved in state-level LPA was conducted. Findings revealed six distinct themes: (1) professional counselor identity, (2) knowledge, attitudes and skills, (3) professional support, (4) power of the group, (5) social justice, and (6) personal impact. Study findings may help counselor educators and supervisors educate, guide, and mentor students, thereby increasing the likelihood of professional counselor LPA. © 2024 Chi Sigma Iota.
Keywords: Counselor education and supervision; counselor advocacy; dept.csp; legislative professional advocacy; professional identity

Fighting for Social Justice - McPherson, Erin A. Harper, Casey, David Shriberg (Handbook of University and Professional Careers in School Psychology, 2020)
Although a much older concept, it is only within the decade of 2010–2019 that this term “social justice” came into prominence in school psychology. This chapter provides a combination of research analysis and a push to personalize and apply the concept of social justice. The chapter begins by defining social justice and describing why this concept is so critical for school psychologists. As part of this overview of social justice, the authors share some of their own stories as examples of how professionals might draw upon their own value systems and experiences to develop as agents of social justice. Readers are also provided with reflection questions to personalize the concept. The bulk of the chapter focuses on what it might look like to “fight” for social justice in school psychology, highlighting concepts such as developing critical self-awareness (with coverage of implicit bias and cultural humility) and using one’s leadership skills to work in an inclusive, participatory manner. A personal action plan template is provided. The chapter closes with a call to action, framing social justice as a mechanism for maximizing both the professional impact and personal satisfaction of one’s work as a school psychologist.
Num Pages: 14
Keywords: dept.csp

Making Choices and Reducing Risk (MCARR): School Counseling Primary Prevention of Substance Use - Foss-Kelly, Louisa L.; Generali, Margaret M.; Crowley, Michael J. (Professional Counselor, 2021)
The consequences of adolescent drug and alcohol use may be serious and far-reaching, forecasting problematic use or addictive behaviors into adulthood. School counselors are particularly well suited to understand the needs of the school community and to seamlessly deliver sustainable substance use prevention. This pilot study with 46 ninth-grade students investigates the impact of the Making Choices and Reducing Risk (MCARR) program, a drug and alcohol use prevention program for the school setting. The MCARR curriculum addresses general knowledge of substances and their related risks, methods for evaluating risk, and skills for avoiding or coping with drug and alcohol use. Using a motivational interviewing framework, MCARR empowers students to choose freely how they wish to behave in relation to drugs and alcohol and to contribute to the health of others in the school community. The authors hypothesized that the implementation of the MCARR curriculum would influence student attitudes, knowledge, and use of substances. Results suggest that the MCARR had a beneficial impact on student attitudes and knowledge. Further, no appreciable increases in substance use during the program were observed. Initial results point to the promise of program feasibility and further research with larger samples including assessment of longitudinal impact.
0 citations (Crossref) [2023-10-31] ERIC Number: EJ1312406
Keywords: Adolescents; Counselor Role; Decision Making; Grade 9; Health Behavior; High School Students; Knowledge Level; Prevention; Program Effectiveness; Risk; School Counseling; School Counselors; Student Attitudes; Substance Abuse; Urban Schools; dept.csp; peer-reviewed

Addressing Student Poverty Using the I-CARE Model in School Counselor Preparation - Generali, Margaret M.; Foss-Kelly, Louisa L. (Journal of Professional Counseling: Practice, Theory & Research, 2022)
The I-CARE Model provides a guiding structure to consider poverty related factors and their impact on people living in poverty. I-CARE encourages counselor trainees to internally reflect on one’s own knowledge, experiences and unintended bias; develop strategies to cultivate relationships with clients; acknowledge realities of living in poverty; and explore interventions to remove barriers. We describe how the I-CARE model may be applied to training school counselors to serve students impacted by poverty. Implications of the model’s use in school counselor preparation are explored, including practical suggestions and directions for future research.
0 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/15566382.2022.2091081
Keywords: I-CARE; Poverty; counselor education; dept.csp; peer-reviewed; school counselor preparation

Development and validation of the peer assessment motivation scale (PAMS) in higher education - Guo, Xiuyan; Liu, Jin; Tang, Hengtao; Gao, Ruiqin; Chen, Qu; Wolfer, Terry; Haynes, Aisha (Studies in Higher Education, 2023)
Measurement of students’ peer assessment motivation is critical to understand how they participate in such activities in higher education. The current study was conducted to develop and validate a brief scale that measures student peer assessment motivation in higher education using the Expectancy-Value Theory (EVT). Initial items were developed, revised, and administered to 369 students. Exploratory factor analyses suggested a three-factor model structure (ability belief, expectancy, and task value) aligning with EVT. Confirmatory factor analyses (n = 399) supported a higher-order factor structure with the three first-order factors (i.e. ability belief, expectancy, and task value) with a decent model fit. The 20-items Peer Assessment Motivation Scale (PAMS) had decent internal reliability, test-retest reliability, convergent validity, and discriminant validity, suggesting that it is a high-quality measure. This scale is beneficial for instructors and researchers who are interested in investigating peer assessment motivation in higher education.
0 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/03075079.2023.2191648
Keywords: Peer assessment motivation; dept.csp; higher education; instrument; peer-reviewed; reliability; validity

What’s COVID-19 Got to Do With It? Implementing the 2020 Connecticut Comprehensive School Counseling Framework - Trombly, Christopher E.; Parzych, Jennifer L.; Generali, Margaret M.; Yavuz, Olcay (Professional School Counseling, 2022)
The Connecticut Comprehensive School Counseling Framework was released in November 2020?8 months into the COVID-19 pandemic. The purpose of this mixed-methods study was to explore the progress made by principals and school counselors in implementing the new framework, and to understand the impact of the pandemic on their efforts to do so. We found significant overlap between the perceptions and priorities expressed by participating principals and school counselors. Particularly noteworthy was the fact that both groups described increased collaboration within their schools.
1 citations (Crossref) [2023-10-31]
Keywords: dept.csp; dept.edl; peer-reviewed

Understanding and Responding to Affectional and Transgender Prejudice and Victimization - Viehl, C.; Ginicola, M.M.; Ellis, A.; Charette, R.J. (Trauma Counseling Theories and Interventions for Managing Trauma, Stress, Crisis, and Disaster: Second Edition, 2022)
In addition to traumas that heterosexual and cisgender people experience, queer and transgender people face a heterosexist and cissexist culture, in which marginalization and trauma against them is normalized or minimized. In this chapter, the experience of hate crimes and violence, relational and interpersonal trauma, religious based-trauma, and sociocultural and political-based trauma are covered in relation to how it impacts Lesbian, Gay, Bisexual, Trans, and Queer (LGBTQ) people. Clinical and counseling implications are discussed. The increase in mental health challenges is explained via the minority stress model. Implications for diagnosis and trauma-informed practices for queer and transgender people are discussed. Additionally, the role of the mental health professional as a social justice advocate is explored, including how social justice frameworks can be incorporated in the counseling environment. © 2023 Springer Publishing Company, LLC and 2012. All rights reserved.
Keywords: dept.csp

Autism and intersectionality: Considerations for school-based practitioners - Sassu, Kari A.; Volkmar, Fred R. (Psychology in the Schools, 2022)
The purpose of this article is to explore the intersectionality of autism and sociocultural factors as well as discuss the complexities associated with appropriate assessment, diagnosis, and intervention. Based on a review of the literature, the authors present a brief history of the emergence of the term autism and highlight factors that have contributed to current concerns about failures to appropriately recognize autism within diverse populations. Referencing extant research as well as professional practice standards, this article examines aspects of autism and intersectionality, and explores some of the associated challenges related to assessment, diagnosis, and intervention. Further, the authors reflect on the critical importance of carefully considering all aspects of a child's identity when engaging in autism assessment and intervention within the school setting. School-based practitioners are provided with guidance for addressing the needs of diverse populations of students with autism.
0 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/pits.22757
Keywords: SES; autism; dept.csp; dept.sed; ethnicity; intersectionality; peer-reviewed; race

Providing primary prevention and school mental health services to LGBTQ+ children and youth: A resiliency-based approach - Rhoades, Elizabeth K. (Incorporating LGBTQ+ Identities in K-12 Curriculum and Policy, 2020)
Keywords: dept.csp

Further exploration in the specialization of school psychology: Graduate training and self-study - Starling, Natalie R.; Elias, Eric M.; Coleman, Mykelle S. (Contemporary School Psychology, 2020)
1 citations (Crossref) [2023-10-31]
Keywords: dept.csp

Preschools and mind-body health - Sassu, Kari A. (Perspectives on Early Childhood Psychology and Education, Special Issue: Promoting Wellness in Preschoolers, 2020)
Keywords: dept.csp

School Counseling Programs Identifying Academic Development Needs - Parzych, Jennifer L.; Generali, Margaret; Yavuz, Olcay (Journal of Education, 2021)
This study examined student, parent, and faculty perceptions of academic development needs and related comprehensive school counseling program services from four urban middle and high schools. Participants (n = 1,032) completed a survey designed to assist schools in planning and evaluating their career and college readiness programs, and exploring perceived student support needs. Statistically significant differences were observed in stakeholder perceptions among 12 identified interventions that support improved academic development, through factorial analysis of variance (ANOVA) and pairwise comparisons analysis. Findings provide valuable information about prioritizing student academic counseling services strategically and effectively, to meet program needs of students in high-poverty schools.
1 citations (Crossref) [2023-10-31]
Keywords: academic development; college readiness; dept.csp; dept.edl; peer-reviewed; poverty; school counselors

Opening the Educational Leadership Door: Promoting the Collaboration of OBM and Education - Starling, Natalie R.; Vissicchio, Carly; Grottke, Katharine (Journal of Organizational Behavior Management, 2020)
What is the future of the relationship between Organizational Behavior Management (OBM) and education? This article presents a discussion of some current issues in education as opportunities for the integration of OBM frameworks and practices. Opportunities are examined in the context of systems-level supports and leadership in education. We hypothesize that an integration of OBM principles and applications has the potential to help educators address multiple critical issues in the field of education, specifically: (a) educator needs at the individual-level, such as educator burnout, engagement, and performance; (b) implementation fidelity of system-wide initiatives and evidence-based interventions; and (c) educator needs at the leadership-level, particularly the training of educational leaders. Recommendations for how OBM researchers and practitioners can expand engagement with educational settings are explored. Given the impact of organizational leadership, we emphasize the future collaboration between OBM and educational leadership, specifically the inclusion of OBM principles and applications in pre-professional curricula and professional continuing education training.
1 citations (Crossref) [2023-10-31] WOS:000588522000001
Keywords: Education; cross-discipline; dept.csp; educational leadership; educator needs; peer-reviewed

Written emotional expression in schools: Processing psychological and emotional stress through narrative writing. - Sassu, Kari A.; Bray, Melissa A.; Gelbar, Nicholas; Kerzner, Tiffany P. (Promoting mind–body health in schools: Interventions for mental health professionals., 2020)
tex.ids: sassuWrittenEmotionalExpression2020a
Keywords: dept.csp

Students’ perceptions of career counselling: an examination of a graduate curriculum in the United States - Lindo, Natalya A; Ceballos, Peggy L; Blalock, Sarah; Conner, Charmaine; Edwards, Josh; Spellings, Maria; Webster, Lindsay; Opiola, Kristie (British Journal of Guidance & Counselling, 2020)
Despite its importance as a core counselling competency, less attention is given to career counselling than to other counselling specialties and it is often dismissed as a non-essential category in the counselling field. Because students’ perceptions of career counselling are affected by peer and faculty attitudes it is important to examine the training needs and experiences of graduate counselling students. Therefore, in the current study we utilised a phenomenological approach to examine students’ perceptions of a career counselling curriculum, and its impact on overall views of career counselling. Analysis of in-depth interviews yielded five major themes: View of Career Counselling, Course Delivery, Theory, Application of Knowledge, and Connection between Career Counselling and Personal Counselling. © 2019 Informa UK Limited, trading as Taylor & Francis Group.
1 citations (Crossref) [2023-10-31] tex.ids: lens.org/071-399-916-740-600, lindoStudentsPerceptionsCareer2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85074340531 tex.type: [object Object] type: Article
Keywords: Career counselling; career theory; counselling theory; counsellor education; dept.csp; peer-reviewed; personal counselling